2022
DOI: 10.1111/jfd.13680
|View full text |Cite
|
Sign up to set email alerts
|

Haematology reference values for Dicentrarchus labrax and Sparus aurata: A systematic review and meta‐analysis

Abstract: Haematological parameters are frequently used as physiological indicators in aquaculture studies. These parameters also have extended applications in clinical evaluation, diagnosis and prognosis in fish health status. However, no normal reference range of values has been demonstrated in depth for any of these haematological parameters for the European sea bass (Dicentrarchus labrax) or gilthead seabream (Sparus aurata). The main objective of this article is to present for the first time through extended litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 112 publications
0
1
0
Order By: Relevance
“…To observe toxicity-induced alterations, it is necessary to provide reference values. Unfortunately, as in all poikilothermic vertebrates, the internal environments of fish are variable and considerably affected by external conditions, and it is very difficult to establish reliable hematological reference values for a species since their ranges are very wide [ 11 , 12 , 13 ]. Witeska et al [ 14 ] summarized the data obtained over eight years from 146 clinically healthy juvenile individuals of Cyprinus carpio used as controls in various studies carried out under similar environmental conditions, and the results showed different levels of variability in various hematological parameters; some of them were stable (e.g., frequency of lymphocytes), most were moderately variable (e.g., hemoglobin concentration and red blood cell count), while others turned out to be highly variable (e.g., thrombocyte count).…”
Section: Hematological Analysis In Fish Toxicologymentioning
confidence: 99%
“…To observe toxicity-induced alterations, it is necessary to provide reference values. Unfortunately, as in all poikilothermic vertebrates, the internal environments of fish are variable and considerably affected by external conditions, and it is very difficult to establish reliable hematological reference values for a species since their ranges are very wide [ 11 , 12 , 13 ]. Witeska et al [ 14 ] summarized the data obtained over eight years from 146 clinically healthy juvenile individuals of Cyprinus carpio used as controls in various studies carried out under similar environmental conditions, and the results showed different levels of variability in various hematological parameters; some of them were stable (e.g., frequency of lymphocytes), most were moderately variable (e.g., hemoglobin concentration and red blood cell count), while others turned out to be highly variable (e.g., thrombocyte count).…”
Section: Hematological Analysis In Fish Toxicologymentioning
confidence: 99%